Impact of Job Stressors Factors on Employees’ Intention to Leave Mediated by Job Engagement and Dispositional Factors - Ramamurthi, Kavitha; Vakilbashi, Amin; Rashid, Siti Zaleha Abdul; Mokhber, Mozhdeh; Basiruddin, Rohaida (International Review of Management and Marketing, 2016)
The purpose of this study is to determine the relationship between job stressors factors, job engagement factors (job stress, job commitment and job satisfaction), job dispositional factors (locus of control, self-esteem and social support from peers and supervisors) and the employees’ intention to leave. Due to that this study is proposed a framework to study the impact of job stressors factors on employees’ intention to leave moderated by job engagement factors and job dispositional factors. The findings can be used by the firm employers or management to take necessary approach to reduce high turnover rate in their companies. Keywords: Job Stressors, Job Engagement, Dispositional Factors, Employees’ Intention to Leave. JEL Classifications: M100, M140, M0